2002
DOI: 10.1038/nature00767
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the recognition of hydroxyproline in HIF-1α by pVHL

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a transcriptional complex that controls cellular and systemic homeostatic responses to oxygen availability. HIF-1 alpha is the oxygen-regulated subunit of HIF-1, an alpha beta heterodimeric complex. HIF-1 alpha is stable in hypoxia, but in the presence of oxygen it is targeted for proteasomal degradation by the ubiquitination complex pVHL, the protein of the von Hippel Lindau (VHL) tumour suppressor gene and a component of an E3 ubiquitin ligase complex. Capture of HIF-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
612
1
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 669 publications
(636 citation statements)
references
References 29 publications
14
612
1
9
Order By: Relevance
“…This approach identified the HIF PHDs as the products of genes related to C.elegans egl-9, a gene that was first described in the context of an egg-laying abnormal phenotype [25]. In mammalian cells, three PHD isoforms were identified (PHD 1-3), and shown to hydroxylate HIF-α in vitro [26][27]. These enzymes have an absolute requirement for oxygen as the substrate.…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach identified the HIF PHDs as the products of genes related to C.elegans egl-9, a gene that was first described in the context of an egg-laying abnormal phenotype [25]. In mammalian cells, three PHD isoforms were identified (PHD 1-3), and shown to hydroxylate HIF-α in vitro [26][27]. These enzymes have an absolute requirement for oxygen as the substrate.…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
“…The overall reaction results in insertion of one oxygen atom into the HIF-α peptide substrate at the proline residue, with the other oxygen molecule generating succinate from 2-OG with the release of CO 2 . Reactions conducted in a limited oxygen environment have revealed that the activity of the purified enzyme is strikingly sensitive to diminished levels of oxygen in vitro [26][27]. The three enzymes have different tissue distributions and, at least under conditions of overexpression, have distinct patterns of subcellular localization [15,19].…”
Section: Hif Is Protective For Mucosal Inflammationmentioning
confidence: 99%
“…HIF-1 constitutes an oxygen-dependent a-subunit and a constitutively expressed b-subunit that interact through mutual basic helix-loop-helix domains [2]. HIF-1a oxygen-dependent domain undergoes site-specific proline hydroxylation by prolyl hydroxylases, which allows subsequent ubiquitination mediated by the von Hippel-Lindau protein [3][4][5]. In the absence of molecular oxygen, HIF-a hydroxylation is abrogated, leading to its cellular accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…7 In its hydroxylated form HIF-1a is recognized by the von Hippel Lindau tumor suppressor protein and targeted for ubiquitination and subsequent proteasomal degradation. 8,9 Upon stabilization of HIF-1a and heterodimerization with HIF-1b, HIF-1 regulates the cellular and systemic response to environmental changes in oxygenation. In tumor tissue, the HIF-1-induced gene expression influences tumor growth and impairs tumor response to chemotherapy and radiotherapy.…”
mentioning
confidence: 99%